2021
DOI: 10.1021/acsnano.0c09758
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Scale Integration of Graphene-Based Photonic Devices

Abstract: Graphene and related materials can lead to disruptive advances in next-generation photonics and optoelectronics. The challenge is to devise growth, transfer and fabrication protocols providing high (≥5000 cm 2 V –1 s –1 ) mobility devices with reliable performance at the wafer scale. Here, we present a flow for the integration of graphene in photonics circuits. This relies on chemical vapor deposition (CVD) of single layer graphene (SLG) matr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 112 publications
3
90
1
1
Order By: Relevance
“…high-speed (>200 GHz) 6 , 7 and broadband (ultraviolet to far-infrared) 8 , 9 operation that could lift bandwidth (BW) (~100 GHz) 10 , 11 and spectral (<1600 nm) 12 limitations of existing technologies, such as Ge/Si 13 , 14 and InGaAsP/InP 15 , 16 . A variety of waveguide (WG)-integrated SLG-based photonic devices have been reported 17 34 , including electro-absorption (EAMs) 17 19 and electro-refraction modulators (ERMs) 20 , optical switches 4 , 21 , and photodetectors (GPDs) 22 33 . SLG and layered materials can be integrated with passive Si photonic WGs 22 27 or any other passive WG technology 4 , including Si 3 N 4 29 , 34 , 35 , sapphire 36 , Ge 37 , and polymers 38 , 39 , extending the spectral range and scope of possible applications 37 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…high-speed (>200 GHz) 6 , 7 and broadband (ultraviolet to far-infrared) 8 , 9 operation that could lift bandwidth (BW) (~100 GHz) 10 , 11 and spectral (<1600 nm) 12 limitations of existing technologies, such as Ge/Si 13 , 14 and InGaAsP/InP 15 , 16 . A variety of waveguide (WG)-integrated SLG-based photonic devices have been reported 17 34 , including electro-absorption (EAMs) 17 19 and electro-refraction modulators (ERMs) 20 , optical switches 4 , 21 , and photodetectors (GPDs) 22 33 . SLG and layered materials can be integrated with passive Si photonic WGs 22 27 or any other passive WG technology 4 , including Si 3 N 4 29 , 34 , 35 , sapphire 36 , Ge 37 , and polymers 38 , 39 , extending the spectral range and scope of possible applications 37 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“… 47 , we showed that it is possible to achieve high mobilities ~30,000 cm 2 V/s at room temperature in wet transferred, polycrystalline 1LG. Thus, scalable processes, such as wet transfer, can be used for integration and packaging 47 , 48 . All these characteristics make 1LG promising as a protective overcoat for both existing and HAMR-based technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane (supported by the frame) was then laminated to the target substrate in air using a dedicated transfer setup. [75] Finally, the polymer was removed in acetone and isopropanol.…”
Section: Methodsmentioning
confidence: 99%